Synergy of MSMEs with People’s Funds to Increase the Prosperity of the Mosque - sriyono, sriyono - (ITB AAS INDONESIA Surakarta, 2024)
This study investigates the moderating role of locus of control in financial management behaviour. The primary aim is to examine how locus of control influences the relationship between determinants and financial management behaviour. Utilizing a quantitative research approach, survey data were collected from a sample of participants. Financial management behaviour and locus of control were measured using validated scales. Statistical analyses, including regression and moderation analysis, were conducted to explore the moderating effects. Results indicate that individuals with an internal locus of control exhibit more proactive financial management behaviours compared to those with an external locus of control. Moreover, locus of control moderates the impact of financial knowledge on financial management behaviour but does not moderate the influence of financial attitudes and income. These findings underscore the importance of considering locus of control in financial planning and education programs, suggesting targeted strategies to enhance financial management behaviours